2001
DOI: 10.1074/jbc.m005770200
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Phosphorylation by Protein Kinase A in CDC25Mm/GRF1, a Guanine Nucleotide Exchange Factor for Ras

Abstract: Activation of the neuronal Ras GDP/GTP exchange factor (GEF) CDC25Mm/GRF1 is known to be associated with phosphorylation of serine/threonine. To increase our knowledge of the mechanism involved, we have analyzed the ability of several serine/threonine kinases to phosphorylate CDC25Mm in vivo and in vitro. We could demonstrate the involvement of cAMP-dependent protein kinase (PKA) in the phosphorylation of CDC25Mm in fibroblasts overexpressing this RasGEF as well as in mouse brain synaptosomal membranes. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
0
26
1
1
Order By: Relevance
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Phosphorylation at this site was not, however, recorded in in vitro experiments with PKA and recombinant Ras-GRF1 by Baouz et al (47). The basis for this difference is unclear, but the current study provides further in vivo support for this PKA-dependent phosphorylation through demonstration of stimulation of Ser 916/898 phosphorylation by forskolin treatment.…”
Section: Phosphorylation Of Ras-grf1 At Ser 916/898mentioning
confidence: 51%
“…Nevertheless, there is strong support for the concept that Ras-GRF1 is highly expressed in certain central neurons and has the potential to play critical roles in processes (such as memory) to which Ras signaling has previously been linked (3,45,46). In this regard, it is interesting to note that Ras-GRF1 is regulated by cAMP/ PKA phosphorylation (26,47), signaling elements that are thought to play a key role in synaptic plasticity and hence memory storage in the brain (17). The identification of activated Ras-GRF1 in the apical dendrites of prefrontal pyramidal neurons in this study is completely consistent with its postulated role as an integrator of neuronal signal transduction (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PKA can cause activation of Src family kinases that feed into Ras pathways in some neuronal and fibroblast cell lines (Klinger et al, 2002). Moreover, a number of molecules that modulate Ras family proteins are substrates for PKA (Baouz et al, 2001). These include a GTPase activating protein known as neurofibromin, the product of the neurofibromatosis-1 gene (Ballester et al, 1990;Martin et al, 1990;Xu et al, 1990;Izawa et al, 1996;Tokuo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%